Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Complete the square and write in standard form: $x-a=A(y-b)^2$
$9y^2-6y-9-x=0$

I do not know how to complete the square with $4$ terms. I started off like: $$9y^2-6y-9=x$$
I don't know whether to start trying to complete the square or if I would do this: $$9y^2-6y=x+9$$
And then complete the square. If someone can either tell me the first one or second one that would be very helpful. Thanks!

EDIT:
$$9y^2−6y=x+9 \\ (3y)^2 - 2 \cdot 3 y + 1^2 = x + 9 + 1 \\ (3y - 1)^2 = x + 10 \\ 9\left ( y - {1 \over 3}\right )^2 = x + 10$$

share|cite|improve this question
up vote 3 down vote accepted

$$ 9y^2−6y=x+9 \\ (3y)^2 - 2 \cdot 3 y + 1^2 = x + 9 + 1 \\ (3y - 1)^2 = x + 10 \\ 9\left ( y - {1 \over 3}\right )^2 = x + 10$$

share|cite|improve this answer

$9y^2-6y-9+x=9(y^2-(6/9)y-1)+x=9(y^2-2.y.(1/3)+(1/3)^2-1/9-1)+x=9(y-1/3)^2-10+x$

and you are done.

share|cite|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.